2018
DOI: 10.1093/humrep/dey026
|View full text |Cite
|
Sign up to set email alerts
|

Secreted frizzled-related protein 2 (SFRP2) expression promotes lesion proliferation via canonical WNT signaling and indicates lesion borders in extraovarian endometriosis

Abstract: This study was funded by the Academy of Finland and by Tekes: Finnish Funding Agency for Innovation. The authors have no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…12 In addition, Tabib et al 13 show DPP4 expression in FBs of both dermal layers in human skin, and suggest a novel major FB population characterized by co-expression of DPP4 and secreted frizzled related protein 2 (SFRP2), a soluble modulator of Wnt signaling. 17,18 However, most of the relevant literature on the role of DPP4-expressing skin fibroblasts still originates from mouse studies. Rinkevich et al demonstrated that a distinct DPP4-expressing lineage of FBs in the mouse skin was responsible for elevated ECM deposition and fibrosis during scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, Tabib et al 13 show DPP4 expression in FBs of both dermal layers in human skin, and suggest a novel major FB population characterized by co-expression of DPP4 and secreted frizzled related protein 2 (SFRP2), a soluble modulator of Wnt signaling. 17,18 However, most of the relevant literature on the role of DPP4-expressing skin fibroblasts still originates from mouse studies. Rinkevich et al demonstrated that a distinct DPP4-expressing lineage of FBs in the mouse skin was responsible for elevated ECM deposition and fibrosis during scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CSCL12 may promote the proliferation, migration and invasion of endometriosis ( 30 ). In addition, CYP1B1 ( 31 ), ETS1 ( 32 ), IGF1 ( 33 ), NOS3 ( 34 ), SFRP2 ( 35 ) and SLIT3 ( 36 ), which were previously identified to serve important roles in endometriosis, were positively correlated with LINC01279.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, mutations of multiple cancer-associated genes are linked to endometriosis, like oncogene of KRAS and antioncogenes of PTEN and TNF [8]. Nevertheless, the pathogenesis of endometriosis is still not well understood since a lack of targeted medical treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt signaling pathway is one of the well-known key cascades that regulate stemness and development, and the function of the Wnt signaling pathway in oncogenesis is presented in many types of tumors [13]. A recent study has revealed that secreted frizzled-related protein 2 (SFRP2) regulates the growth of endometriosis lesions and indicates the borders of endometriosis lesions together with CTNNB1, functioning as a typical stimulant of Wnt/CTNNB1 signaling pathway in endometriosis [9]. Furthermore, the engraftment and survival of desquamated endometrium are critically dependent on angiogenesis, and the Wnt/β-catenin signaling pathway plays a significant role in driving neovascularization [14].…”
Section: Introductionmentioning
confidence: 99%